Texture Synthesis Based on Vector Field and Application in Textile and Clothing (Journal of Fiber Bioengineering and Informatics, 2015)
Texture is indispensable in image-based rendering. In order to obtain realistic and aesthetic texture, asimple and effective texture synthesis method based on vector field is presented in this paper. A sufficientlarge, progressively-variant, aperiodic texture can be generated from a small texture sample based onthe proposed method. The main contributions in this method are anisometric synthesis and appearancecontrol. Anisometric synthesis is attained by using an expanded sample structure called the warpingimage stack, together with a quadrant searching step and a continuity matching approach. Appearancecontrol is achieved by associating each partition of the texture to a certain guiding vector, which arrangesthe partition to have corresponding local rotation and scaling. The experiments show that our methodcan produce textures with natural and flexible effect.